Neutralizing Antibody Titers In Post-Covid-19 Patients And Post-Covid Pneumonia: Prognostic Value And Clinical Course (Texas Journal of Medical Science, 2025)
Pneumonia and delayed inflammatory processes observed in the post-COVID period are associated with multiple pathophysiological mechanisms. Neutralizing antibody (NAb) titers represent a key component of the immune response to the virus, and their levels may influence disease severity, duration, and the course of post-COVID syndrome. This article analyzes the relationship between NAb titers, hematological parameters (Hb, erythrocytes, leukocytes, color index, ESR), and the clinical progression of post-COVID pneumonia in a cohort of unvaccinated patients examined after recovering from COVID-19 pneumonia.